Sustainability and Economic Attributes of Peer-To-Peer Accommodation: A Cross Country Perception of Asian Tourists - Mark Ratilla; Sandeep Dey; Harry Jay Cavite; Therese Ratilla; Miloslava Chovancov (My University, 2021)
Peer-to-peer (P2P) accommodation has expanded the range of offerings in the tourism and hospitality sector.The study explores the familiarity, usage and overall perception towards P2P accommodation among tourists in the Philippines, Thailand and India.It investigates the association among perceived economic benefits, environmental sustainability and socio-demographic characteristics on tourists' overall perception.A web-based survey was deployed in the first quarter of 2020, right in the onset of Covid-19 pandemic.As the travel frequency of tourists cannot be initially ascertained and to capture their usage in the "normal" times, a recall query with respect to their usage over the past six months (June-December 2019) was utilized.Descriptive statistics and non-parametric statistical tests were employed for data analysis.The findings reveal that the familiarity of Thai tourists lags behind other nationalities.Majority have not used P2P accommodation for the past six months; however, overall perceptions remain positive for both active and non-active users.Across nationalities, respondents somewhat agreed on the nuance of economic benefits and environmental sustainability.Moreover, analysis shows its significant positive association with tourists' overall perception.
Keywords: Cross country; Sharing Economy and Platforms